2010
DOI: 10.1111/j.1744-7429.2009.00549.x
|View full text |Cite
|
Sign up to set email alerts
|

Frugivory and Seed Dispersal by the Lowland Tapir Tapirus terrestris in the Peruvian Amazon

Abstract: The lowland tapir Tapirus terrestris is the largest herbivore in the Neotropics and feeds on a large quantity of fruits, often ingesting the seeds and defecating them intact. Seed dispersal by the lowland tapir in the southwestern Amazon was studied by examining seeds from 135 dung samples collected between 2005 and 2007. Seeds of a total of 122 plant species were identified, representing 68 genera and 33 families. The species accumulation curve showed that more species can be expected with further sampling. M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
65
3
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 66 publications
(76 citation statements)
references
References 49 publications
(80 reference statements)
3
65
3
3
Order By: Relevance
“…Indeed, T. terrestris and T. bairdii have often been observed foraging in patches of secondary vegetation (Naranjo 1995, Salas & Fuller 1996, Foerster & Vaughan 2002, Tobler 2002. The same pattern has been observed in other animal groups (Bowen et al 2007), reinforcing the hypothesis that tropical secondary forests may benefit part of the fauna (Wright & Muller-Landau 2006). The tapir's diet comprises mainly vegetative plant parts.…”
Section: Diet Of the Lowland Tapirsupporting
confidence: 60%
See 2 more Smart Citations
“…Indeed, T. terrestris and T. bairdii have often been observed foraging in patches of secondary vegetation (Naranjo 1995, Salas & Fuller 1996, Foerster & Vaughan 2002, Tobler 2002. The same pattern has been observed in other animal groups (Bowen et al 2007), reinforcing the hypothesis that tropical secondary forests may benefit part of the fauna (Wright & Muller-Landau 2006). The tapir's diet comprises mainly vegetative plant parts.…”
Section: Diet Of the Lowland Tapirsupporting
confidence: 60%
“…Based on collectors'curve approach (plotting accumulated number of the species against sampling effort), the studies for the lowland tapir showed that 53 fecal samples (Hibert et al 2011), 94 fecal samples (Barcelos et al 2013), and even 135 fecal samples (Tobler et al 2010) could not be adequate to estimate the diet richness of this ungulate. Regarding deer species, Gayot et al (2004) observed that 28 stomachs of the red brocket and that 34 stomachs of the grey brocket were both insufficient to assess suitably these ungulates diet (in terms of plant species).…”
Section: Sampling Design and Procedures Used In The Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies on the diet of T. terrestris described these animals as important dispersers, due to the diversity and quantity of seeds that they consume, the long distances traveled from the parent tree (Bachand et al, 2009;Bizerril et al, 2005;Bodmer, 1991;Golin et al, 2008;Tobler et al, 2010), and also because large seeds depend on large fruigivores that may be rare or absent (Lazure et al, 2010). According to quantitative and qualitative criteria suggested by Schupp (1993), tapirs may be considered good dispersers of B. tomentosa, as they frequently visited trees, consumed a large quantity of ripe fruits, and defecated viable seeds in favorable sites for germination.…”
Section: Discussionmentioning
confidence: 99%
“…Another evidence that supports this observation is that only seeds were found in feces of tapirs, after fruit maturation and natural drop, suggesting that the consumption of these fruits occurs only on the ground when fruits are accessible to these animals. According to Bodmer (1991) and Tobler et al (2010), tapirs forage in different habitats and have a broad diet, but the availability and abundance of fruits are decisive in the choice of food items.…”
Section: Discussionmentioning
confidence: 99%